Two-dimensional thio- and seleno-cyanates of Mo and W. (9th November 2017) - Boukouvala, C; Kaltsas, D; Tsetseris, L
Abstract: The stability of two-dimensional (2D) transition metal di-chalcogenides (TMDC) is controlled by the fact that sulfur or selenium atoms can cap the 2D layers without exposing highly reactive bonds. Here we use first-principles calculations to show that a similar structural motif can stabilize Mo- and W-based 2D materials with thio- or seleno-cyanate groups. In particular, we show that the formation of Mo(SeCN)2, W(SCN)2 and W(SeCN)2 sheets is energetically favorable and can lead to various configurations that resemble the well-known polymorphs of TMDCs. The lowest-energy structures are small-gap semiconductors, while certain polytypes bear Dirac-like cones close to the Fermi energy, demonstrating the potential of these new 2D materials for applications in modern electronic devices.